2006
DOI: 10.1073/pnas.0510213103
|View full text |Cite
|
Sign up to set email alerts
|

Costs and benefits of priming for defense in Arabidopsis

Abstract: Induced resistance protects plants against a wide spectrum of diseases; however, it can also entail costs due to the allocation of resources or toxicity of defensive products. The cellular defense responses involved in induced resistance are either activated directly or primed for augmented expression upon pathogen attack. Priming for defense may combine the advantages of enhanced disease protection and low costs. In this study, we have compared the costs and benefits of priming to those of induced direct defe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
615
0
9

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 750 publications
(640 citation statements)
references
References 40 publications
16
615
0
9
Order By: Relevance
“…This is not illogical, because activation of inducible defenses involves major costs that affect plant growth and reproduction [57], and this is inconsistent with the beneficial nature of these plant-microbe interactions. Through the study of the costs and benefits of priming in Arabidopsis, it was recently shown that the fitness costs of priming are lower than those of constitutively activated defenses, such as those expressed in the constitutive SAR-expressing mutant cpr1 [58 ]. Intriguingly, the fitness benefits of priming outweighed its costs under pathogen pressure, which suggests that priming functions as an ecological adaptation of the plant to respond faster to its hostile environment.…”
Section: Resultsmentioning
confidence: 99%
“…This is not illogical, because activation of inducible defenses involves major costs that affect plant growth and reproduction [57], and this is inconsistent with the beneficial nature of these plant-microbe interactions. Through the study of the costs and benefits of priming in Arabidopsis, it was recently shown that the fitness costs of priming are lower than those of constitutively activated defenses, such as those expressed in the constitutive SAR-expressing mutant cpr1 [58 ]. Intriguingly, the fitness benefits of priming outweighed its costs under pathogen pressure, which suggests that priming functions as an ecological adaptation of the plant to respond faster to its hostile environment.…”
Section: Resultsmentioning
confidence: 99%
“…A recent field study confirmed that SAR increases the fitness of plants exposed to pathogens, which translates into enhanced crop yield [52]. However, unlike the fitness cost of constitutive resistance that associated with inducible resistance generally appears to outweigh the cost of pathogen infection, although this might depend on additional environmental factors [53,54 ]. In the era of metabolomics, large-scale surveys might reveal additional candidate compounds involved in SAR induction (e.g.…”
Section: Signal Perception and Amplificationmentioning
confidence: 99%
“…Priming for defence against pathogens has been shown to involve considerably fewer costs than the induction of direct defence, and the benefits derived from this priming outweigh the costs under conditions of disease pressure [12]. The phenomenon of volatile-induced priming against insects also fits in this ecological context of costs and benefits.…”
Section: The Role Of Hipvs In Indirect Plant Defencesmentioning
confidence: 99%
“…In addition, we address the recent studies that point to a priming effect in plants that are exposed to certain HIPVs, conferring an enhanced defensive capacity against future insect attack [6 ,7-11]. We conclude, with some reservations, that there is not only reason for optimism that manipulation of HIPVs emissions can indeed lead to enhanced repulsion of pests and attraction of their natural enemies but, moreover, that enhanced volatile information transfer between plants might, if exploited appropriately, improve the efficiency of the plant's direct and indirect defence strategies through priming [4,12]. Figures 1 and 2 summarize the various interactions in which HIPVs are implicated as we have studied them for maize plants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation